Rapid Sequence Intubation pada Pasien Hamil Ektopik dengan COVID-19 Ringan yang Menjalani Laparotomi Histerektomi - Wisudarti, Calcarina Fitriani Retno; Adiyanto, Bowo; Naomi, Diah Anis (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Female patient aged 27 years was diagnosed with ectopic pregnancy in ampulla vateri, grade II hemorrhagic shock resolved, G2P1A0 8 weeks 5 days pregnant, mild COVID-19, underwent exploratory laparotomy and hysterectomy. The patient did not have any complaints of fever, cough, shortness of breath, and anosmia. The patient was diagnosed with mild COVID-19 because of a positive SARS-CoV-2 Qualitative PCR swab and no pneumonia. The operation was carried out in a special operation room for airborne infection patients with a HEPA filter machine installed. General anesthesia intubation using the RSI technique. No difficult airway was found in the patient. No Sellick maneuver was performed. Patient was intubated with a direct laryngoscope. The ETT position was confirmed by capnograph. After the operation, the patient was extubated deeply, then returned to the ward. There was no perioperative complication in this patient.